Optimalisasi Peran Ibu Tunggal (Janda) dalam Membangun Ekosistem Bisnis Pedesaan melalui Ekonomi Sirkular untuk Meningkatkan Value Added Produk Pertanian di Desa Gandasoli - Nurul Siti Jahidah; Oktaviani Rita Puspasari; Neng Evi Kartika (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
This community service program was implemented to optimize the role of single mothers in developing a rural business ecosystem through a circular economy approach to increase the value added of agricultural products in Gandasoli Village. The program aimed to empower the Srikandi Gandasoli community to process sweet potato agricultural waste into marketable products, manage small businesses independently, and expand market access. The implementation methods consisted of socialization through focus group discussions, production training, business and financial management training, digital marketing training, and assistance in obtaining business legality supported by production equipment and materials. The results indicate a significant improvement in participants’ understanding and skills related to production processes, business management, financial management, packaging design, digital marketing, and business licensing, as reflected in their active participation and enthusiasm throughout the activities. The program also created new business opportunities based on agricultural waste, reduced production costs, expanded product marketing reach, and strengthened social solidarity and economic independence among participants. This initiative contributes to the development of a sustainable rural business ecosystem and supports increased household income. It is recommended that the program continue with advanced training to expand business scale and open wider market opportunities.